Diels‐Alder Reaction Mechanisms of La@C60 and Gd@C60 Studied Using Density Functional Theory - Cui, Cheng‐Xing; He, Jun‐Ru; Qu, Ling‐Bo; Li, Chun‐Xiang; Peng, Jia‐Li; Maseras, Feliu (Chemistry : a European journal, 2024)
Encapsulation of transition metals represents a crucial method for modifying the electronic structure and regulating the reactivity of fullerene, thereby expanding its applications. Herein, we present calculations with density functional theory methods to investigate the mechanisms of the Diels‐Alder (DA) reactions of cyclopentadiene and La@C60 or Gd@C60 as well as their tricationic derivatives. Our findings indicate that the encapsulation of La and Gd into the C60 cage is thermodynamically favorable. The DA reactions are favored by the presence of La and Gd, with lower barriers, though the regioselectivity, favoring 6−6 bonds in the fullerene, is not affected. The effect of external electric fields has been also considered. Improving the understanding of fullerene reactivity through calculation. DFT calculations reproduce and rationalize the behaviour of endohedral fullerenes containing lanthanum of gadolinium centers, either in cationic or neutral form, towards Diels‐Alder reactions. These results can be extrapolated to the reactivity of other endohedral fullerenes with other dienes.